ANALISIS ALIRAN BALIK (BACKWATER) PADA AMBANG GERIGI - harsanti, ST., MT, winda; Efendi, Medi; Riskijah, Sitti Safiatus (Prokons: Jurnal Teknik Sipil, 2020)
Gerigi weir is a modificated jigsaw weir which can hold water flow to gain higher water level. This water raising happens in upstream of the weir until certain length to reach normal depth. This research uses square open channel model with slope as an independent variable. In this research uses various slope from 1‰ to 5‰ for eight different discharges. The aim of this research is to find the impact of slope for backwater length using Direct Step Method. The result of this research is the longest back water happened in the 8th of experiment discharge (1399,984 cm3/sec) with the slope of 3‰, by 40.800,4952 cm from the weir. In addition, slope is not affect for the length of backwater. This is because from all analysis of experiments, the longest backwater happens in different slope for each discharge, namely between 1‰, 3‰, or 4‰ of slope.                      Keywords: back water, gerigi weir, slope